Espaço Europeu de Ensino Superior e a Literacia Informacional : conceitos e objectivos de um projecto de pesquisa aplicada em Ciência da Informação - Armando Malheiro da Silva (2008)
This paper takes as general reference the European Higher Education Area ( EHEA) , wliose creation endeavoured an educative approach of all EuropeanUnion counlries. A new educational model needs new skills. The informational skills constitute one of the most important required by a university student inthe information society. So it is important to know how these university students are prepared in terms of competences and skills, in the use, articulation anddiffusion of the information gathered and applied in different contexts. It is also necessary to establish a connection between apprenticeship and acquisition of informational skills in high school and in university, and, with this information, to contribute to the definition of a strategy that allows Portuguese universities a goodperformance in the ability and skills to search and use of information. This article emphasizes in the information literacy theory, necessary to develop this kind of research.